2017
DOI: 10.1016/j.ynpai.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The grimace scale reliably assesses chronic pain in a rodent model of trigeminal neuropathic pain

Abstract: The limited success in translating basic science findings into effective pain management therapies reflects, in part, the difficulty in reliably assessing pain in experimental animals. This shortcoming is particularly acute in the field of chronic, ongoing pain. Quantitative analysis of facial expressions—the grimace score—was introduced as a promising tool, however, it is thought to reliably assess only pain of short or medium duration (minutes to hours). Here, we test the hypothesis that grimace scores are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 50 publications
9
88
0
1
Order By: Relevance
“…We used a rodent model of neuropathic pain, evoked by chronic constriction of the infraorbital nerve (CCI-ION) (Vos et al, 1994;Benoist et al, 1999;Okubo et al, 2013;Akintola et al, 2017;Castro et al, 2017a). We first anesthetized animals with isoflurane, followed by ketamine/xylazine (i.p.).…”
Section: Induction Of Chronic Orofacial Painmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a rodent model of neuropathic pain, evoked by chronic constriction of the infraorbital nerve (CCI-ION) (Vos et al, 1994;Benoist et al, 1999;Okubo et al, 2013;Akintola et al, 2017;Castro et al, 2017a). We first anesthetized animals with isoflurane, followed by ketamine/xylazine (i.p.).…”
Section: Induction Of Chronic Orofacial Painmentioning
confidence: 99%
“…To assess ongoing pain, we analyzed facial grimace behavior (Langford et al, 2010;Sotocinal et al, 2011;Akintola et al, 2017Akintola et al, , 2019. We placed animals in a square Plexiglas™ chamber (6×8 inches for rats, 3x5 inches for mice) with two opaque sides and two transparent sides on a raised wire platform.…”
Section: Grimace Scalementioning
confidence: 99%
See 1 more Smart Citation
“…One of the potential applications of I/P ratio analysis could be in laboratory animal welfare, where currently the grimace scale is used to measure the degree of pain/stress. [38][39][40][41][42][43] I/P ratio analysis could be integrated to grimace scale scores to refine the efficiency and sensitivity of progressively detecting animal in pain/stress. Although this study was focused on primates, we see the general principle of this work is applicable to all species.…”
Section: Discussionmentioning
confidence: 99%
“…To allow reliable and reproducible quantification of pain-related expressions, Mogil and collaborators developed facial grimace scales for mice (Langford et al, 2010) and for rats (Sotocinal et al, 2011) and demonstrated that these objective metrics have high accuracy and reliability for detecting ongoing pain of relatively short duration (minutes to hours). This approach has been shown to be a reliable and sensitive metric for the assessment of ongoing pain in a rodent model of chronic, trigeminal neuropathic pain in both rats and mice (Akintola et al, 2017). With these experimental components in hand, it would be possible to set out to test the hypothesis that placebo analgesia can be conditioned in animals suffering from chronic pain.…”
Section: Future Directionsmentioning
confidence: 99%